Pediococcus acidilactici in the culture of turbot (Psetta maxima) larvae: Administration pathways - Villamil, L.; Figueras Huerta, Antonio; Planas, Miguel; Novoa, Beatriz (Aquaculture, 2010)
6 páginas, 4 figuras Probiotic administration to marine fish larvae and live prey has been shown to be a useful means to prevent bacterial infection and mass mortalities. Here, several experiments were carried out in order to determine the optimum protocol for Pediococcus acidilactici delivery to the turbot (Psetta maxima) gastrointestinal tract by its administration via rotifers supplemented for 1 or 24 h with the bacteria or directly via the water. The survival capacity of P. acidilactici in sterile seawater, in microalgae (Isochrysis galbana) culture and in rotifers (Brachionus plicatilis) was determined, with best results in rotifer culture. The incorporation of P. acidilactici into the rotifer's gut was time-dependant, with P. acidilactici recovery from rotifer cultures supplemented with the lactic acid bacteria suspension for 24 h being significantly lower than from cultures supplemented for 1 h. Similarly, P. acidilactici recovery from the gastrointestinal tract of turbot larvae was higher when larvae were fed with 1-h supplemented rotifer cultures. However, significantly higher P. acidilactaci recovery from turbot larvae gastrointestinal tract was observed when the probiotic was directly administered in the rearing water. Lastly, the bactericidal activity of the extratracellular products (ECPs) of P. acidilactici against a pathogenic bacterium for turbot, Vibrio splendidus (Hm 112) was assessed. The ECPs of P. acidilactici significantly inhibited the growth of the pathogenic bacteria in vitro. However, during in vivo experiments, the bacterial community, dominated mainly by Vibrio and Pseudomonas, was not apparently affected by P. acidilactici supplementation in rotifers or turbot larvae. This work was partially supported by the project 1FD97-0044- C03-02/03 from FEDER. Peer reviewed